Determining the Dominant Contributions between Direct and Indirect Impacts of Long-Term Urbanization on Plant Net Primary Productivity in Beijing - Yuan Chen; Dangui Lu; Bo Xu; Rui Ren; Zhichao Wang; Zhongke Feng (Remote Sensing, 2024)
Rapid urbanization exerts noteworthy impacts on the terrestrial ecosystem carbon budget, with pronounced effects in a metropolis such as Beijing, the capital city of China. These impacts include both Direct and Indirect Impacts. For instance, direct impacts influence regional Net Primary Productivity (NPP) by directly altering the vegetation coverage area. Concurrently, indirect impacts primarily affect regional NPP indirectly through climate change and urban vegetation management. How direct and indirect impacts contribute to the NPP is the core content of our research. Owing to that, we need to precisely assess the spatial and seasonal characteristics of the impact of urbanization in Beijing from 2000 to 2020. Firstly, a novel framework was proposed to analyze the impact of urbanization on NPP at the pixel level. Meanwhile, we employ the Proximity Expansion Index (PEI) to analyze urban expansion patterns. Results reveal that the direct impacts led to a cumulative NPP loss of 0.98 TgC, with the largest loss stemming from cropland conversion to construction land. During the last two decades, there has been a 56.87% increase in the area used for urban development in Beijing, a clear sign of swift urban expansion. Concurrently, this urban growth has had favorable indirect effects on NPP, with an average annual increase of 9.76 gC·m−2·year−1, mainly observed in urbanized regions. Moreover, the seasonal analysis underscored that indirect impacts were primarily temperature-related, exhibiting higher values during autumn and winter within urban areas, indicating enhanced vegetation growth suitability in urban areas during these seasons. Our findings quantitatively examine the numerical relationship between direct and indirect impacts at a magnitude level. The carbon gain brought about by indirect impacts surpassed the carbon loss induced by direct impacts, with indirect impacts offsetting 29.41% of the carbon loss due to direct impacts. Ultimately, we advocate for enhanced greening initiatives in areas of Beijing with higher indirect impacts to achieve optimal carbon gain. This strategy might effectively reduce the negative impact of rapid urbanization on the carbon budget of terrestrial ecosystems.